Polyboramines for Hydrogen Release: Polymers Containing Lewis Pairs in their Backbone. (13th November 2015) - Ledoux, Audrey; Larini, Paolo; Boisson, Christophe; Monteil, Vincent; Raynaud, Jean; Lacôte, Emmanuel
Abstract: The one‐step polycondensation of diamines and diboranes triggered by the in situ deprotonation of the diammonium salts and concomitant reduction of bisboronic acids leads to the assembly of polymer chains through multiple Lewis pairing in their backbone. These new polyboramines are dihydrogen reservoirs that can be used for the hydrogenation of imines and carbonyl compounds. They also display a unique dihydrogen thermal release profile that is a direct consequence of the insertion of the amine–borane linkages in the polymeric backbone. Abstract : Polymerer H2 ‐Spender : Die einstufige Polykondensation von Diamin‐ und Diboran‐Vorstufen führt zu Polymerketten mit Lewis‐Paaren als Verbindungsstücken (siehe Schema). Diese neuartigen Polyboramine wirken als Diwasserstoff‐Reservoire, die Imine, Aldehyde und Ketone hydrieren können. Die thermische H2 ‐Freisetzung verläuft nach einem einzigartigen Profil, was eine direkte Folge der polymeren Natur des Materials ist.